2020
DOI: 10.1212/nxi.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

NK cell markers predict the efficacy of IV immunoglobulins in CIDP

Abstract: ObjectiveTo assess whether IV immunoglobulins (IVIgs) as a first-line treatment for chronic inflammatory demyelinating polyneuropathy (CIDP) have a regulative effect on natural killer (NK) cells that is related to clinical responsiveness to IVIg.MethodsIn a prospective longitudinal study, we collected blood samples of 29 patients with CIDP before and after initiation of IVIg treatment for up to 6 months. We used semiquantitative PCR and flow cytometry in the peripheral blood to analyze the effects of IVIg on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Ahmadi et al demonstrated that a low dose of IVIG upregulated inhibitory receptors and decreased activating receptors, which coincided with a decrease in natural cytotoxicity by PBMCs from women with recurrent spontaneous abortion (10). Additionally, Mausberg et al found that multiple NK receptors, including CD94, were downregulated at the transcriptional level in PBMCs post IVIG infusion of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) (33). After a high dose of IVIG, we did not observe similar changes in the receptors but did find a marked decrease in both the expression of the granule exocytosis marker, CD107a, and in cytotoxicity that was most striking in the clinically homogenous KD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmadi et al demonstrated that a low dose of IVIG upregulated inhibitory receptors and decreased activating receptors, which coincided with a decrease in natural cytotoxicity by PBMCs from women with recurrent spontaneous abortion (10). Additionally, Mausberg et al found that multiple NK receptors, including CD94, were downregulated at the transcriptional level in PBMCs post IVIG infusion of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) (33). After a high dose of IVIG, we did not observe similar changes in the receptors but did find a marked decrease in both the expression of the granule exocytosis marker, CD107a, and in cytotoxicity that was most striking in the clinically homogenous KD group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Mausberg et al. found that multiple NK receptors, including CD94, were downregulated at the transcriptional level in PBMCs post IVIG infusion of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) ( 33 ). After a high dose of IVIG, we did not observe similar changes in the receptors but did find a marked decrease in both the expression of the granule exocytosis marker, CD107a, and in cytotoxicity that was most striking in the clinically homogenous KD group.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that a subgroup of patients with sustained immunological remission confounded the results due to a subjective IVIg response and continued to receive IVIg, which is in line with a recent study which demonstrated that the placebo effect is a common challenge after long‐term immunoglobulin treatment in CIDP [27]. Furthermore, the reduction of NK dim cell frequencies after IVIg administration, also a marker for IVIg response [19], was not significantly different to that in SCIg recipients. Likewise, myeloid dendritic cells were not differentially altered by IVIg and SCIg in CIDP.…”
Section: Discussionmentioning
confidence: 70%
“…This latter effect is important in CIDP since impaired B-cell maturation and reduced CD32b expression on B cells and monocytes are IVIg-responsive features [17]. Furthermore, IVIg treatment reduces myeloid dendritic cells and cytotoxic natural killer cells (NK dim ) that are also involved in the pathogenesis of CIDP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Then, by preliminary screening of innate immune cells (mast cells, macrophages, MDSCs, neutrophils, and natural killer cells) and adaptive immune cells (B cells and CD8 + T cells) in the cholangiocarcinoma, we observed that NNMT was specifically associated with the gene signature of macrophages and MDSC (Figures S2B, C http://links.lww.com/HEP/A36). [14][15][16][17][18] Therefore, this study further detected the infiltration of these 2 cells in GBC.…”
Section: Nnmt Is Overexpressed In Human Gbc and Is Associated With Im...mentioning
confidence: 85%